FOOD SAFETY CULTURE ASSESSMENT. SARS-CoV-2 PERSPECTIVE - Małgorzata Z. Wiśniewska; Eugenia Czernyszewicz; Tomasz Grybek (International Journal for Quality Research, 2023)
This paper investigates the phenomenon of food safety culture (FSC) from the perspective of SARS-CoV-2-related hazards. The importance of FSC in the context of organizational culture, and its role in strengthening the quality and food safety management system were explained. The aim of the article is to propose the tool to measure and assess the level FSC concerning the risk connected with SARS-CoV-2 contamination. The SARS-CoV-2-based FSC assessment tool have been developed and the reliability of this tools have been confirmed. It was possible to identify the overall and the partial FSC levels in seafood company and to show which variables most significantly affect the employees behavior, and beliefs against food safety, and based on that areas for further improvement. The tool propsed by us may be applied by various food entities, especially those interested in meeting the mandatory requirements contained in the current EU food law.